TINJAUAN KRIMINOLOGIS TERHADAP PENYALAHGUNAAN NARKOTIKA DIKALANGAN PELAJAR DI WILAYAH HUKUM POLISI RESORT KOTA PEKANBARU - Goklan Tamba; Syaifullah Yophi A; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Adolescence is transition periode, where at the time of such instability is often the case that emotional and psychological well. That's what makes teenagers or students often perform deviant behavior such as juvenile delinquency said. Juvenile delinquency is a collection of various teenage behavior that is socially unacceptable causing criminal action. Juvenile delinquency is a lot going such as smoking, fighting, and narcotics. The number teenagers who fall into drug abuse to environmental factors such as promiscuity is not supervised parents, from broken home, as well curiosity so try using narcotics. Based on above description essay aims to determine the factors that cause crime drug abuse among students in the jurisdiction Police Resort Pekanbaru, know modus operandi the drug abuse, determine effort Police made Pekanbaru to the prevention and drug abuse among students.This type of research is conducted legal research Sociological. The data used is primary data collected directly from the writing of this paper the author uses research methods that are field, The results; First, the factors influence occurrence of the crime of drug abuse in Pekanbaru, among others : the first factor is less parental attention , and felt alienated, second factor environment in which people live, and the third is the taste factor curious and try that led to the crime of drug abuse. The modus operandi of perpetrators criminal acts committed by drug abuse among adolescents narotics easily obtained and used at night, Third prevention efforts and precautions taken handling crime of drug abuse among adolescents in Pekanbaru with preventive and repressive.Keyword : Criminologicalcrime – Narkotics - Student